Note—A Graphical Aid for Determining Optimal Inventories in a Unit Replenishment Inventory System - Silver, Edward A.; Smith, Stephen A. (Management Science, 1977)
This note provides the methodology to construct a set of indifference curves that permit the exact determination of the optimal inventory level in a system where items are restocked one at a time and unsatisfied demand is lost. An illustrative set of curves is shown.